Dobra Orla przed przejęciem ich przez Radziwiłłów birżańskich - Sierba, Michał (Acta Universitatis Lodziensis. Folia Historica, 2013)
This text concerns the history of the Orla assets before 1585, up to the Bierżan Radziwiłł’s takeover. Through descriptions of political conflicts and settler movements the author presents the story of the Orla possessions up to the turn of fifteenth and sixteenth century, which is the time when first written sources covering this issue became available. Those days the first municipalities constituting the Orla assets were noted. Michajło Bohusz Bohowitynowicz took control over Topczykały, Werweczki and Koszele with its surroundings. Those villages became a cornerstone for building and developing the possessions followed by the brisk colonization action by Bohowitynowicz and his successors: daughter Anna – wife of Stanisław Tęczyński and granddaughter Catherina – wife of George Olelkowicz Słucki. The text also presents the conflicts involving the ownership of the Orla assets, marking out and delimiting their borders, e.g. including the Koszki village in 1562. Most important part of the article is based on the presentation of detailed data from the tax register of 1570s, which brings a complete information about the scale and status of those assets. The comparison analysis between the Orla possessions and other properties of the Bielsk Land and Podlasie summarizes the article.